ANALISIS PERSEPSI MASYARAKAT DALAM MEMILIH PERBANKAN SYARIAH DI KOTA BATAM - Raymond Raymond; Nanda Harry Mardika (Yayasan Akrab Pekanbaru, 2018)
One reason people choose a Bank is whether the Bank can provide benefits and convenience for them, nationally the growth of sharia banking has increased, but specifically for Riau Islands Province the growth of sharia banking actually decreased, based on these problems by using cochran Q test analysis tools the researcher tried to study whether there are factors influencing customer decision in saving in syariah bank in Batam city, and Is there any dominant factor influencing customer decision in saving in syariah bank in Batam city, the result of this research found that the existence of factors that influence the decision of the customer in saving in syariah bank in Batam City, In addition from variable external the most dominant in influencing customer decision in saving in syariah bank in Batam City that is on cultural factor at cultural indicator of State and pr factor omosi on the indicators of convenience and internal variables are the most dominant in influencing customer decisions in savings in Islamic banks in the city of Batam that is the factor of service on the indicator Courtesy of the employees and facilities factor on the indicator ATM. Keywords: Bank Syariah, Cochran Q test, and Pepsepsi analysis.